Bimbingan Keagamaan Pada Santri Tingkat Wustho II (Perilaku Kebiasaan Ghasab di Pondok Pesantren Darussalam Sumbersari Kediri) - M. Dhiya’udin; Mustajib (LP3M IAIFA Kediri, 2021)
The behavior of the ghasab is generally said to have entrenched the environment of boarding school, it implies that the act of using the property of others illegally for self-interest has often happened and both the students, teachers and administrators have considered this as something normal and common in their environment, can not be separated from one of them is students of Darussalam boarding school. The purpose of this activity is to give full understanding to students to reduce, eliminate and even break the chain of ghasab culture in environment of boarding school and also remind every ghasab behavior never justified in the teachings of Islam and also the rule of law in our country. Method of implementation of this activity through presentation, lecture, and reciprocal interaction between students with sources for 60 minutes in the classl of boarding school Darussalam. The result of this activity is the absorption of understanding about the impact of ghasab behavior, either from the meaning of Islamic law as well as state law and also the long-term impact of ghasab behavior for the character formation in the future.